2017
DOI: 10.1128/mbio.02014-16
|View full text |Cite
|
Sign up to set email alerts
|

A Reverse Genetics Platform That Spans the Zika Virus Family Tree

Abstract: Zika virus (ZIKV), a mosquito-borne flavivirus discovered in 1947, has only recently caused large outbreaks and emerged as a significant human pathogen. In 2015, ZIKV was detected in Brazil, and the resulting epidemic has spread throughout the Western Hemisphere. Severe complications from ZIKV infection include neurological disorders such as Guillain-Barré syndrome in adults and a variety of fetal abnormalities, including microcephaly, blindness, placental insufficiency, and fetal demise. There is an urgent ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
75
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 54 publications
2
75
0
Order By: Relevance
“…In fact, a recent study has shown that a single amino acid substitution (A188V) in the viral NS1 protein is critical for NS1 antigenemia, which in turn facilitates ZIKV acquisition by mosquitoes from viremic animals (24). With the availability of infectious clones of ZIKV (25)(26)(27)(28)(29)47) from historical and contemporary isolates, it will be possible to further examine the specific changes in the viral genome that are responsible for viral transmission, replication, virulence, and tissue tropism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, a recent study has shown that a single amino acid substitution (A188V) in the viral NS1 protein is critical for NS1 antigenemia, which in turn facilitates ZIKV acquisition by mosquitoes from viremic animals (24). With the availability of infectious clones of ZIKV (25)(26)(27)(28)(29)47) from historical and contemporary isolates, it will be possible to further examine the specific changes in the viral genome that are responsible for viral transmission, replication, virulence, and tissue tropism.…”
Section: Discussionmentioning
confidence: 99%
“…We set out to examine if N-linked glycosylation within the VNDT motif plays any role in ZIKV pathogenicity in an immunocompromised-mouse model. Although infectious clones of MR766 viruses (25,28,29), as well as several other ZIKV isolates (26,27,47), have been reported, the role of VNDT or glycosylation in this region in pathogenicity has not been explored. A recent study using ectopic expression and pseudoparticle formation with a WNV replicon showed that N-glycosylation of ZIKV E protein is necessary for efficient particle assembly and infectivity (48).…”
Section: Discussionmentioning
confidence: 99%
“…A series of approaches (14,15,24,28,(50)(51)(52) have been applied for the generation of ZIKV reverse genetics platforms. Since direct assembly of the native ZIKV full genome in E. coli had been successful only in a few cases (14,50), most established reverse genetics systems of ZIKV were based on either in vitro assembly of viral cDNA fragments (24,52) or eukaryotic intron-based and HCMV promoter-driven, "infectious DNA" clones (15,28).…”
Section: Discussionmentioning
confidence: 99%
“…Since direct assembly of the native ZIKV full genome in E. coli had been successful only in a few cases (14,50), most established reverse genetics systems of ZIKV were based on either in vitro assembly of viral cDNA fragments (24,52) or eukaryotic intron-based and HCMV promoter-driven, "infectious DNA" clones (15,28). In the present study, we successfully utilized the group II intron P.li.LSUI2 to stabilize the cDNA clone of ZIKV in a commonly used E. coli host strain.…”
Section: Discussionmentioning
confidence: 99%
“…Although ZIKV was first identified more than 70 years ago (1), its ability to cause congenital infection and fetal malformations was discovered only after the explosive 2015 epidemic in South America, where more than 1.5 million people were infected (2). Some have speculated that genetic evolution of ZIKV may have contributed to some of the new clinical manifestations identified in the recent outbreaks ( 3, 4 ). Indeed, the emergence of a mutation in the prM gene (S139N) in post-epidemic strains was associated with greater infectivity and injury of neuroprogenitor cells (5).…”
Section: Introductionmentioning
confidence: 99%